Thermoregulatory responses during prolonged intermittent exercise at the same workload - Lin, J.; Ouer, A.; Nshiba, M. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction: Intermittent exercise is a common feature of many sports. Thus, it is important to understand the physiological responses to intermittent exercise. Previous studies on intermittent exercise have largely been focused on the body`s respiratory and circulatory responses; however, a few studies have considered the thermoregulatory response to intermittent exercise. These studies indicate that the increase in internal temperature during intermittent exercise (30-s intervals of exercise and rest) was greater than that during continuous exercise, and that intermittent exercise was associated with lower sweat loss relative to continuous exercise at the same heat production (Ekblom et al., 1971). In addition, it was shown that the increase in internal temperature during intermittent exercise depends on the exercise period (Astrand et al., 1960). However, these studies were conducted at high exercise intensity ( 100% workload compared with continuous exercise). Therefore, in this study we investigated the effect of different exercise periods on the thermoregulatory responses during medium intensity intermittent and continuous exercise at same total workload. Methods All experiments were conducted at 25 C and 50% relative humidity. Exercise was performed under three different conditions: 1) Continuous exercise at 50% maximal oxygen uptake (VO ) for 30 min (con-condition), 2) Intermittent exercise at 50% VO for 60min (30-s intervals of exercise and rest; 30-s condition), and 3) Intermittent exercise at 50% VO2max for 60min (3-min intervals of exercise and rest; 3-min condition). In each experiment, the subject`s heart rate, blood pressure, rectal temperature, skin temperature (forehead, chest, upper arm, forearm, thigh and calf), sweating rate, skin blood flow (forehead, chest and forearm), perceived exertion and oxygen uptake were measured. Results Heart rate, mean arterial pressure and perceived exertion were higher in con-condition than in the 30-s and 3-min condition, whereas no difference in heart rate was observed under the 3-min condition compared with 30-s condition. A greater increase in rectal temperature was noted during the 30-s condition than in the con- and 3-min conditions, while oxygen uptake and total sweat loss were higher in the con-condition than the other two conditions. Discussion / Conclusions Rectal temperature in the 30-s condition was higher than that in the other conditions, with lower sweat loss relative to con-condition. This indicates that thermoregulatory efficiency may be lower during intermittent exercise than during continuous exercise at the same workload, even at a mild intensity. Moreover, during intermittent exercise, shortening of the exercise period may cause a decrease in the efficiency.